(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
Stylistics, a bridge between linguistics and literary criticism, explores how linguistic elements shape the style and meaning of texts. This article examines the types of stylistics, including literary, linguistic, and computational approaches, and their applications in English. Key phonetic features like alliteration, assonance, and onomatopoeia are analyzed for their aesthetic and emotional effects. Lexical-morphological elements, such as diction, idiomatic expressions, and neologisms, reveal the richness of word choice and formation. Grammatical features, including sentence structure, ellipsis, and parallelism, demonstrate how syntax contributes to tone and emphasis.